Development Of Practical Module In Bakery Courses At Food Science And Culinary Education Study Program Universitas Negeri Semarang - Marie Curie Habibah; Saptariana; Asih Kuswardinah; Pudji Astuti (Jurnal Sains Boga, 2023)
The practical module is one of the teaching materials, used as a guide for students. In this research, an easy, effective, and efficient practical module will be made so it can be used as a reference for practicel bakery subject in Food Science and Culinary Education Study Program at UNNES. In this research we used Research and Development (R&D) methods. With the development method developed by S. Thiagarajan et al, namely the four-D (4D) development method which consists of define, design, develop, and disseminate. The data collection technique was carried out by conducting FGDs with a material expert also a media expert to get some knowledge in order to the practical module being made properly. After the module being completed, validation will be carried out through questionnaires to three material experts and 3 media experts, which thoroughly documented. The analytical method used in this research were the aiken validity test and interrater reliability test using the Intraclass Correlat Coefficients (ICC) reliability. The results of the aiken validity test based on media experts were 0,84 with the criteria for a valid assessment having high validity. Meanwhile the results of the aiken validity test for material experts were 0,72 with the criteria for a valid assessment having moderate validity. The results of the media expert’s ICC reliability test were 0,729, interpreted as the rater’s agreement was quite good (moderate), and the results of the material expert ICC reliability test were 0,763, meaning that the rater agreement was good. The overall average value obtained identifies that the bakery practical module is "appropriate" to be used as a learning media because the overall average eligibility standard is categorized as "Good".